An Analysis of Texts Written by Third Semester of Undergraduate Students of English Education Study Program - Maria Goreti Djehatu; Felix Tans; Agustinus Semiun (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This writing aims at finding out the kinds of texts written by the students, analyzing students’ texts’ constructions, and finding out their problems in writing English texts. This study employs descriptive qualitative method. It describes deeply the finding that related to aims of study above. The data of this result is taken from the written forms of English texts by the third semester of the undergraduate students of English Education Study Program of Widya Mandira Catholic University. The research shows that there are six kinds of texts written by the third semester of the undergraduate students of English Study Program of Widya Mandira Catholic University. Those kinds of texts are narrative text, descriptive text, recount text, comparison/contrast text, cause-effect text, and expository text. Some of Students’ text writings are cohesively, coherently and grammatically correct. However, some other students present incohesive, incoherent, and grammatically incorrect in writing English texts. Furthermore, there are several problems faced by the students in writing English texts, namely: transferring ideas in writing, lack of vocabulary, problem in using grammar, difficult to start writing, lack of reading sources, problem in organization of writing, and inconsistent in developing idea.